Предложения с конструкцией for + n/pr + inf как объекты лингвистического анализа - Левинене, А. Б.; Мухин, А. М. (Kalbotyra, 1972)
The present article analyses the inner structure of sentences with for + n/pr + inf and defines syntactic junctions held between the elements.Junctional and componental models are made up to present the distinctive syntactical features of the sentence elements. The deep structure of sentences and the distinctive syntactic-semantical features of their elements are presented by means of syntaxemic models.We arrive at the conclusion that in most cases the construction for + n/pr + inf is not a syntactic complex. Its elements can be defined as two kinds of elementary units: sentence components - possesing distinctive syntactical features - and syntaxemes - possesing distinctive syntactic-semantical features.